Respuesta :

Answer:

Final answer is 13.

Step-by-step explanation:

Given expression is

-k+h+kh

We also have been given values of h and k as:

k=-5 h=-2

to simplify the given expression, we just need to plug the given values of k=-5 and h=-2 into -k+h+kh

-k+h+kh

[tex]=-(-5)+(-2)+(-5)(-2)[/tex]

[tex]=5+(-2)+(-5)(-2) [/tex]

[tex]=5-2+(-5)(-2) [/tex]

[tex]=5-2+(10)[/tex]

[tex]=5-2+10[/tex]

[tex]=3+10[/tex]

[tex]= 13[/tex]

Hence final answer is 13.

Answer:

7

Step-by-step explanation:

you have to put the numbers in for the variables

-5+2+5(2)